Pengaruh Promosi Elektronik dan Inovasi Produk Terhadap Keputusan Pembelian Pada Produk Mixue di Garut - Endah Ridanengsih; Risma Rahma Nisa; Sri Vinka Nabila; Refina Nazza Ilhami; Hilman Rismanto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of electronic promotions and product innovation on purchasing decisions for Mixue products in Garut. The increasingly fierce competition in the contemporary beverage business requires companies to maximize digital marketing strategies and product innovation to maintain consumer interest and purchasing decisions. This study uses a quantitative method with a descriptive-verification approach that aims to determine and analyze the influence of electronic promotions and product innovation on purchasing decisions for Mixue consumers in Garut. The respondents were 100 Mixue consumers in Garut who were selected through a purposive sampling technique. Data analysis was carried out using Partial Least Square – Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results show that electronic promotions have a positive and significant effect on purchasing decisions, which means that the more intense and attractive the digital promotions are, the higher the consumer's tendency to purchase Mixue products. In addition, product innovation also has a positive and significant effect on purchasing decisions, indicating that menu diversity, new flavors, and continuously developed product quality can improve consumer purchasing decisions. These findings confirm that the success of purchasing decisions for Mixue products in Garut is greatly influenced by effective digital promotion strategies and continuous product innovation.